2010
DOI: 10.1111/j.1439-0531.2010.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Conception Rates in Ewes after AI with Ram Semen Preserved in Milk–Egg Yolk Extenders Supplemented with Glycerol

Abstract: This study aimed at comparing the effect of ram semen preserved at 5 °C on two milk-based extenders (UHT skim milk or INRA-96(®) , 5% egg yolk) supplemented with 2% glycerol, and the preservation time (24 and 48 h) on conception rates after cervical AI of ewes. In two field trials, 1198 Merino ewes were cervical AI in spontaneous oestrus. In Experiment 1, pooled semen (6 rams) was extended in UHT-base (fresh, control) or chilled for 24 h in UHT5Y (UHT-base 5% egg yolk), INRA5Y (INRA-96(®) 5% egg yolk), UHT5Y2G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…A similar finding was observed by other scientists (Kasimanickam et al, 2007;Gundogan et al, 2011). Our study revealed that the motility of spermatozoa was reduced with increasing preservation time, however, the mean motile sperm was 75.5% up to 48 h of storage, a time which is acceptable for AI according to Olivera-Muzante et al (2011). Taken together, these results showed that Triladyl gives better support to sperm motility after storage at 4°C than TFE.…”
Section: Discussionmentioning
confidence: 53%
“…A similar finding was observed by other scientists (Kasimanickam et al, 2007;Gundogan et al, 2011). Our study revealed that the motility of spermatozoa was reduced with increasing preservation time, however, the mean motile sperm was 75.5% up to 48 h of storage, a time which is acceptable for AI according to Olivera-Muzante et al (2011). Taken together, these results showed that Triladyl gives better support to sperm motility after storage at 4°C than TFE.…”
Section: Discussionmentioning
confidence: 53%
“…Considerable progress in semen preservation has been made over the past few decades; however, the decline that occurs in sperm quality during this process has not been resolved [5,11,20]. During in vitro preservation, there is a risk of oxidative damage to sperm owing to ROS accumulation [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian sperm membrane contains a large amount of polyunsaturated fatty acids (PUFA). When ROS is excessive, the PUFA of the sperm membrane is attacked, which causes lipid peroxidation (LPO) [10,20]. LPO of sperm membranes can also lead to failure of the acrosome reaction [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paulenz et al (2003) reported a 51.5 and 61.9% lambing rate using semen stored at 5°C diluted in a commercial TRIS-based or milk extender, respectively, in Norwegian Crossbred ewes. The overall conception rate of ewes inseminated with diluted (UHTbase) chilled semen (after 24 h of preservation at 5°C) was significantly lower than the control group inseminated with diluted fresh semen after 1 h of preservation at room temperature (56% vs 74% respectively, P<0.05) (Olivera-Muzante et al 2011).…”
Section: Resultsmentioning
confidence: 81%